2018
DOI: 10.1016/j.bbr.2018.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Chronic amphetamine treatment affects collicular-dependent behaviour

Abstract: Distractibility can be defined as an attention deficit where orientation toward irrelevant targets cannot be inhibited. There is now mounting evidence that the superior colliculus is a key neural correlate of distractibility, with increased collicular-activity resulting in heightened distractibility. Heightened distractibility is reduced by amphetamine, which acutely suppresses collicular responsiveness. However, when amphetamine is used to treat distractibility, it is given chronically, yet no data exist on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
(86 reference statements)
1
2
0
Order By: Relevance
“…This has been found previously for other brain regions following chronic treatment with amphetamine, albeit given intraperitoneally (Peterson et al, 2006). This suppression would be consistent with our behavioural effects previously reported which suggest that chronic amphetamine treatment reduces activity in the colliculus and suppresses collicular dependent behaviour (Turner et al, 2018a).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This has been found previously for other brain regions following chronic treatment with amphetamine, albeit given intraperitoneally (Peterson et al, 2006). This suppression would be consistent with our behavioural effects previously reported which suggest that chronic amphetamine treatment reduces activity in the colliculus and suppresses collicular dependent behaviour (Turner et al, 2018a).…”
Section: Discussionsupporting
confidence: 93%
“…For example, acute amphetamine has been shown to suppress activity in the visually responsive superficial layers of the SC in healthy animals (Dommett et al, 2009;Gowan et al, 2008) and in rodent models of ADHD (Clements et al, 2014). In addition, we have recently demonstrated that chronic treatment with orally-administered amphetamine selectively alters colliculardependent behaviour in a manner consistent with suppression of activity in the area (Turner et al, 2018a). Furthermore, amphetamine is known to act on dopaminergic neurons to increase synaptic dopamine levels, and based on previous research (Rolland et al, 2013) we can infer that this should suppress visual responses in the colliculus.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation